Luminescence Dating of Relics in Ancient Cities Provides Absolute Dates for Understanding Human-Land Relationships in Qinghai Lake Basin, Northeastern Tibetan Plateau - Sun, Manping; Sun, Yongjuan; Wei, Haicheng; Hou, Guangliang; Xianba, Ji; Xie, Liqian; Zeng, Yongxin; E, Chongyi (Frontiers in Earth Science, 2021)
The study of ancient city sites provides valuable evidence for understanding human-land relationships. Qinghai Lake Basin, on the northeastern Tibetan Plateau, was a key location for economic and cultural exchanges between East and West in ancient China and archaeological surveys have identified the remains of many ancient cities. Although there are relatively good historical records for some ancient cities, their absolute ages are still unclear due to a lack of systematic chronological dating. In this study, OSL dating of ceramic and tile remains from three ancient cities in Qinghai Lake Basin, Xihaijun (XHJGC), Beixiangyang (BXYGC), and Fuxi (FSC), was combined with documentary and paleoclimate evidence to investigate historical human-land relationships. Relics from XHJGC and BXYGC were dated to 0–220 AD, in the Han Dynasty, while tiles from FSC were dated to 120–520 AD, largely corresponding to the Wei Jin Southern and Northern Dynasties. Luminescence ages were generally consistent with dates recorded in historical documents, indicating that the OSL method can be reliably used to date buried tiles in ancient cities on the northeastern Tibetan Plateau. Comparing the dates with paleoclimatic records suggests that the warm and humid climate at c. 2 ka was an important driver of immigration to the region that led to the construction of cities in the Qinghai Lake area during the late Western Han Dynasty. During the Wei Jin Southern and Northern Dynasties (220–589 AD), communication between East and the West flourished, and human activities in the area were strong with the continuation of the war in Central China and Hexi Corridor. Fuxi was largely abandoned in the later Wei Jin Southern and Northern Dynasties, although it was still used intermittently until the Ming Dynasty. Pollen records confirm that humans were extensively engaged in agricultural production in the Qinghai Lake area during the Wei Jin Southern and Northern Dynasties.